Single-cell analysis uncovers fibroblast heterogeneity and criteria for fibroblast and mural cell identification and discrimination - Lars Muhl (Nature Portfolio, 2020)
To define and distinguish fibroblasts from vascular mural cells have remained challenging. Here, using single-cell RNA sequencing and tissue imaging, the authors provide a molecular basis for cell type classification and reveal inter- and intra-organ diversity of these cell types.